Optimization of water and nitrogen management for surge-root irrigated apple trees in the Loess Plateau of China - Zhi-guang DAI; Liang-jun FEI; Jian ZENG; De-liang HUANG; Teng LIU (Journal of Integrative Agriculture, 2021)
The Loess Plateau is one of the main regions for growing apple trees in China, but a shortage of water resources and low utilization of nitrogen have restricted its agricultural development. A 2-year field experiment was conducted which included three levels of soil water content (SWC), 90–75%, 75–60%, and 60–45% of field capacity, and five levels of nitrogen application (Napp), 0.7, 0.6, 0.5, 0.4 and 0.3 kg/plant. The treatments were arranged in a strip-plot design with complete randomized blocks with three replications. For both years, the water and Napp had significant (P<0.05) effects on leaf area index (LAI), yield, water use efficiency (WUE) and nitrogen partial factor productivity (NPFP) while the interaction effect of water and Napp on yield, WUE and NPFP was significant (P<0.05) in 2018, and not in 2017. For the same SWC level, WUE first increased, then decreased as Napp increased, while NPFP tended to decrease, but the trend of LAI with different Napp was closely related to SWC. At the same Napp, the LAI increased as SWC increased, while the WUE and NPFP first increased, then decreased, but the yield showed different trends as the SWC increased. The dualistic and quadric regression equations of water and Napp indicate that the yield, WUE and NPFP cannot reach the maximum at the same time. Considering the coupling effects of water and Napp on yield, WUE and NPFP in 2017 and 2018, the SWC level shall be controlled in 75–60% of field capacity and the Napp is 0.45 kg/plant, which can be as the suitable strategy of water and Napp management for the maximum comprehensive benefits of yield, WUE and NPFP for apple trees in the Loess Plateau and other regions with similar environments.